Evaluation of SPM Using the Balanced Scorecard to Assess Operational Efficiency at PT BGR Logistik Indonesia - Winda Romanna Aruan; Elok Heniwati; Djunita Permata Indah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study evaluates the role of the management control system through the Balanced Scorecard in improving operational efficiency in the logistics sector. Using a qualitative instrumental case study, data was collected through semi-structured interviews, observations, and document analysis, then analyzed using thematic coding. The findings reveal that the Balanced Scorecard has not functioned optimally as a strategic control tool due to weak integration among performance indicators and inconsistent implementation. Operational efficiency remains partial, particularly in time and process aspects. This study proposes an Adaptive Balanced Scorecard emphasizing system integration and operational flexibility. Keywords: Management Control System; Balanced Scorecard; Operational Efficiency; Adaptive Balanced Scorecard